2009
DOI: 10.4161/auto.5.7.9161
|View full text |Cite
|
Sign up to set email alerts
|

MgAtg9 trafficking inMagnaporthe oryzae

Abstract: Autophagy is a vacuolar/lysosomal cytoplasmic recycling system in eukaryotic cells. ScATG9 is indispensable for autophagy in Saccharomyces cerevisiae. Here, we deleted MgATG9, the orthologue of ScATG9, via targeted gene replacement in the phytopathogenic filamentous fungus Magnaporthe oryzae, and then analyzed the cellular distribution pattern of EGFP-MgAtg9 in the Mgatg9Delta mutant. We detected an expression profile of multiple green dots in the conidial cell inoculated in rich media and in the appressoria d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 45 publications
1
78
1
Order By: Relevance
“…However, such a central structure is not detected in proximity of the vacuoles of moatg13Δ and moatg17Δ mutants. 63 These findings are not consistent with observations in yeast. 64,65 It can be speculated that MoAtg13 and/or MoAtg17 has lost its function in autophagy in M. oryzae and therefore the Atg1-Atg13 complex might not be preserved across all fungi during evolution.…”
Section: Molecular Mechanisms Of Autophagy In Pathogenic Fungicontrasting
confidence: 57%
See 2 more Smart Citations
“…However, such a central structure is not detected in proximity of the vacuoles of moatg13Δ and moatg17Δ mutants. 63 These findings are not consistent with observations in yeast. 64,65 It can be speculated that MoAtg13 and/or MoAtg17 has lost its function in autophagy in M. oryzae and therefore the Atg1-Atg13 complex might not be preserved across all fungi during evolution.…”
Section: Molecular Mechanisms Of Autophagy In Pathogenic Fungicontrasting
confidence: 57%
“…By contrast, the expression pattern of the same fusion proteins is not changed in a moatg13Δ mutant. 63 It was concluded that cycling of MgAtg9 through multiple sites (as indicated by colocalization studies) to its storage pools in the cytosol of M. oryzae depends on MoATG1, MoATG2, and MoATG18, but not MoATG13. Loss of MoATG1, MoATG2 and MoATG18 might prevent MoATG9 from leaving the PASlike structures in M. oryzae.…”
Section: Molecular Mechanisms Of Autophagy In Pathogenic Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…1D), which is consistent with studies in mammals that show the constitutive occurrence of autophagy. 21 Similar to the pattern of Atg protein localization in yeast and Magnaporthe cells, [22][23][24] punctate localization of MrAtg8 was observed in conidia, germlings, appressoria and hyphal bodies (fungal cells harvested from the hemolymph of infected insect) by N-terminal fusion with the red fluorescent protein (RFP) ( Fig. 2A-D).…”
Section: Introductionmentioning
confidence: 90%
“…In the rice blast fungus M. grisea (oryzae), deletion mutants of Mgatg1, Mgatg4, Mgatg5, Mgatg8 and Mgatg9 result in an inability to form the infection structure and loss of the ability of the fungus to infect its plant host (Veneault-Fourrey et al, 2006;Liu et al, 2010Liu et al, , 2007Dong et al, 2009;Lu et al, 2009). In the basidiomycete plant-pathogenic fungus Ustilago maydis, deletion of atg1 or atg8 also blocks autophagy and affects morphogenesis, but the Datg1 strain is only slightly less pathogenic than the wild-type (WT), whereas the Datg8 strain is significantly reduced in fungal pathogenicity (Nadal & Gold, 2010).…”
Section: Introductionmentioning
confidence: 99%